Fernando de Azevedo: Public and Intellectual Trajectory of an Eminently Brazilian Scholar - Pereira, João Paulo Rodrigues (Sententiae, 2025)
The article situates Fernando de Azevedo within the perspective of Brazilian intellectuals who sought to think about Brazil’s cultural reality. Starting from the notion of trajectory as an element that showcases the features of the life path of an eminently Brazilian intellectual, this piece presents a synthesis of the author’s academic career and their intellectual and public work. As a result, it highlights (1) Fernando de Azevedo’s contribution to education and the humanistic nature of his work; (2) some of the influences of sociological and philosophical ideas (particularly related to global trends) on his work; (3) his public participation in both political and educational debates; and (4) his work Brazilian Culture, which contains a specific analysis of Brazilian culture and history.